Functional in vitro characterization of small extracellular vesicles isolated from menstrual blood‐derived mesenchymal stem/stromal cells. (23rd February 2022) - Mahdipour, Elahe
Abstract: Menstrual blood is a rich source of mesenchymal stem/stromal cells (MenSCs) with a diverse potential to differentiate into various cell types. Similar to other cells, MenSCs produce extracellular vesicles from which, small extracellular vesicles have attracted much interest due to their therapeutic and regenerative capacities. Here using in vitro approaches, several properties of MenSC‐derived small extracellular vesicles (MEX) have been investigated. HUVEC angiogenesis assay was used to evaluate the proangiogenic function of MEX. The immune regulatory property of MEX was assessed using a T cell proliferation assay. Proliferation, migration, and gene expression of primary fibroblasts were selected to determine the scar‐related activity of MEX. Finally, the anti‐cancer effect of MEX on the proliferation of cancerous cell lines was tested. Our results demonstrated that the small extracellular vesicles isolated from MenSCs have proangiogenic and immune‐suppressive abilities. Moreover, these vesicles performed as an anti‐proliferative agent for cancerous cell lines. MEX was also able to reduce the migration of primary fibroblasts. In summary, MEX has shown promising in vitro characteristics for regenerative applications. They may offer a great cell‐free strategy with therapeutic potential for a diverse range of diseases. For future therapeutic applications and further clinical translation, more studies are needed to elucidate the involved mechanisms.